Integrated Model for Resilience Evaluation of Power-Gas Systems Under Windstorms - Yucui Wang; Yongbiao Yang; Qingshan Xu (CSEE Journal of Power and Energy Systems, 2024)
Integrated power-gas systems (IPGS) have developed critical infrastructure in integrated energy systems. Moreover, various extreme weather events with low probability and high risk have seriously affected the stable operation of IPGSs. Due to close interconnectedness through coupling elements between the power system (PS) and natural gas system (NGS) when a disturbance happens in one system, a series of complicated sequences of dependent events may follow in another system. Especially under extreme conditions, this coupling can lead to a dramatic degradation of system performance, resulting in catastrophic failures. Therefore, there is an urgent need to model and evaluate resilience of IPGSs under extreme weather. Following this development trend, an integrated model for resilience evaluation of IPGS is proposed under extreme weather events focusing on windstorms. First, a framework of IPGS is proposed to describe states of the system at different stages under disaster conditions. Furthermore, an evaluation model considering cascading effects is used to quantify the impact of windstorms on NGS and PS. Meanwhile, a Monte Carlo simulation (MCS) technique is utilized to characterize chaotic fault of components. Moreover, time-dependent nodal and system resilience indices for IPGS are proposed to display impacts of windstorms. Numerical results on the IPGS test system demonstrate the proposed methods.